Postcards from the trenches : negotiating the space between modernism and the First World War - Booth, Allyson (ACLS Humanities E-Book., 1996)
This study offers a complex portrait of the relationship between British First World War culture and modernist writings. It shows that unlike civilians, modernist writers and combatants shared a concern with the divide between language and experience. Connections are drawn between the sensibility of the modernist writer and the soldier, particularly regarding efforts to describe dying and the dead. The analysis extends to memorials, posters and architecture of the Great War, though the emphasis is on literary works by Robert Graves, E.M. Forster, Vera Brittain and others.